Becoming a graphic designer a guide to careers in design - Heller, Steven; Fernandes, Teresa (John Wiley & Sons, Inc., 2002)
Here is the completely updated guide to today's graphic design careers-a clear and concise survey of the design field, from major design industries to design disciplines. Filled with interviews and advice from leading designers, it covers interactive design, information design, motion, educational training, portfolio preparation, getting a job, and much more: magazine design; advertising book design; corporate identity; film titles; tv graphics; interactive design; environmental design; web design; education; type design; motion; graphics information; graphics package design; record design. Becoming a Graphic Designer provides a comprehensive survey of the graphic design market, including complete coverage of print and electronic media and the evolving digital design disciplines that offer today's most sought-after jobs.